Recreational injury and its relation to socioeconomic status among school aged children in the US. Issue 1 (1st March 2002) - Ni, H; Barnes, P; Hardy, A M
Abstract : Objectives: This study described epidemiologic patterns of recreational injuries among school aged children in the US and assessed the relation of these patterns to socioeconomic status. Methods: Combined data from the 1997–98 National Health Interview Surveys for 38 458 children aged 6–17 years regarding non-fatal recreational injury episodes that received medical attention, reported by a household adult, were analysed. Logistic regression analysis was used to assess the association between recreational injury and socioeconomic status while controlling for confounding factors. Results: The annualized rate of recreational injury was 91.2 episodes per 1000 children, with an increased risk associated with a higher family income status or being non-Hispanic white. For children from not poor families, most injury episodes occurred in sport facilities, whereas for children from poor and near poor families, most occurred outside the home. Conclusion: Recreational injury is a significant health problem for school aged children in the US. Non-Hispanic white children and children from affluent families are at increased risk of recreational injury.